Catalysis of Peroxide Reduction by Fast Reacting Protein Thiols - Zeida, Ari (2019)
Life on Earth evolved in the presence of hydrogen peroxide, and other peroxides also emerged before and with the rise of aerobic metabolism. They were considered only as toxic byproducts for many years. Nowadays, peroxides are also regarded as metabolic products that play essential physiological cellular roles. Organisms have developed efficient mechanisms to metabolize peroxides, mostly based on two kinds of redox chemistry, catalases/peroxidases that depend on the heme prosthetic group to afford peroxide reduction and thiol-based peroxidases that support their redox activities on specialized fast reacting cysteine/selenocysteine (Cys/Sec) residues. Among the last group, glutathione peroxidases (GPxs) and peroxiredoxins (Prxs) are the most widespread and abundant families, and they are the leitmotif of this review. After presenting the properties and roles of different peroxides in biology, we discuss the chemical mechanisms of peroxide reduction by low molecular weight thiols, Prxs, GPxs, and other thiol-based peroxidases. Special attention is paid to the catalytic properties of Prxs and also to the importance and comparative outlook of the properties of Sec and its role in GPxs. To finish, we describe and discuss the current views on the activities of thiol-based peroxidases in peroxide-mediated redox signaling processes.